The Role of Dopamine in Gastric Cancer—A Systematic Review of the Pathogenesis Phenomena Developments - Cimpeanu, Radu-Cristian; Fortofoiu, Dragoș; Sandu, Elena; Dragne, Ioana-Gabriela; Caragea, Mariana-Emilia; Dumitriu-Stan, Roxana-Ioana; Salmen, Bianca-Margareta; Boldeanu, Lidia; Reurean-Pintilei, Delia Viola; Vere, Cristin-Constantin (Biomedicines, 2024)
Background: In the last few decades, it has been emphasized that dopamine, a well-known neurotransmitter with multiple roles in central nervous system, is also implicated in the activity of peripheral tissues and organs, more specifically influencing the gastrointestinal system (GI). Methods: We registered a protocol under the CRD42024547935 identifier in the Prospero register of systematic reviews. Furthermore, using the Population, Intervention, Comparison, Outcome, and Study Design strategy to guide our study rationale, and under the Preferred Reporting Items for Systematic reviews and Meta-Analyses recommendations, we conducted a qualitative systematic literature search based on the PubMed, Scopus, and Web of Science databases using the “gastric cancers AND dopamine” search criteria. We obtained 68 articles from PubMed, 142 articles from Scopus, and 99 articles from the Web of Science database. Results: Within gastric cancer biology, dopamine has notable effects on STAT-3 and DARPP-32. STAT-3, a transcription factor involved in cellular proliferation and invasion, plays a significant role in cancer progression. Conclusions: Understanding the roles of dopamine in cancer, beyond aspects such as cancer cell invasion, immune response modulation, or tumor growth, could guide the development of new cancer therapies by modulating its pathways, especially the DARPP-32/CXCR4/CXCL-12 complex axis, in order to improve the morbidity and mortality caused by this type of cancer.